A Review of Islamic Law on the Target of Grocery Stores - Tassya Ramadhaningsih; Daud; Alisyah Pitri (Zabags Qu Publish, 2025)
This study explores the integration of Islamic business ethics into marketing practices as a foundation for promoting fairness, transparency, and sustainability in contemporary business activities. The main objective is to examine how ethical principles derived from Islamic teachings influence marketing strategies and consumer trust. Using a qualitative approach, this research synthesizes findings from academic literature to identify thematic patterns and conceptual relationships relevant to the application of Shariah-compliant values in marketing. The results indicate that ethical values such as honesty, fairness, and trustworthiness are consistently emphasized in Islamic business practices and are significantly associated with building strong customer relationships and long-term business credibility. Furthermore, the review highlights trends in recent scholarly works that demonstrate the increasing relevance of ethics in digital marketing contexts, where the challenges of misinformation and consumer manipulation are more prevalent. The contribution of this study lies in providing a theoretical and practical framework that can guide businesses, policymakers, and scholars in strengthening ethical marketing practices grounded in Islamic values.